2005
DOI: 10.1105/tpc.105.031625
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and Light Control of Adventitious Rooting in Arabidopsis Require ARGONAUTE1

Abstract: Adventitious rooting is a quantitative genetic trait regulated by both environmental and endogenous factors. To better understand the physiological and molecular basis of adventitious rooting, we took advantage of two classes of Arabidopsis thaliana mutants altered in adventitious root formation: the superroot mutants, which spontaneously make adventitious roots, and the argonaute1 (ago1) mutants, which unlike superroot are barely able to form adventitious roots. The defect in adventitious rooting observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
310
1
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 361 publications
(339 citation statements)
references
References 62 publications
12
310
1
9
Order By: Relevance
“…An Arabidopsis transgenic line overexpressing ARF17 developed fewer adventitious roots than wild-type plants, confirming the potential role of ARF genes in the regulation of adventitious root development by auxin (Sorin et al, 2005). It was shown that ARF17, a target of miR160, is a negative regulator, and ARF6 and ARF8, targets of miR167, are positive regulators of adventitious rooting.…”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 72%
“…An Arabidopsis transgenic line overexpressing ARF17 developed fewer adventitious roots than wild-type plants, confirming the potential role of ARF genes in the regulation of adventitious root development by auxin (Sorin et al, 2005). It was shown that ARF17, a target of miR160, is a negative regulator, and ARF6 and ARF8, targets of miR167, are positive regulators of adventitious rooting.…”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 72%
“…miR164 regulates auxin signals for lateral root development by targeting NAC mRNA cleavage (Guo et al, 2005). miR167 regulates plant development by negatively regulating the expression of several AUXIN RESPONSE FACTORS (ARF), including ARF 2, ARF 3, ARF 4, ARF 10, ARF 16, and ARF 17 (Mallory et al, 2005;Sorin et al, 2005;Williams et al, 2005a;Yang et al, 2006). miRNAs regulate phase change in plants.…”
Section: Functions Of Micrornas In Plantsmentioning
confidence: 99%
“…This adaptive mechanism involves suppressing lateral root initiation on the dry side of a root Bellini et al (2014) and formatting based on Hochholdinger et al (2004b). The original description of the mutant phenotypes detailed in the table can be found in: Boerjan et al (1995), Delarue et al (1998), Fukaki et al (2002), Sorin et al (2005), Sibout et al (2006), Dello Ioio et al (2007), and Negi et al (2010 …”
Section: Prebranch Site Formationmentioning
confidence: 99%